Analisis Pembelajaran Mewarnai Menggunakan Krayon dengan Metode Drill untuk Pengembangan Motorik Halus Anak Usia Dini Usia 3-4 Tahun di Sanggar WARNA Tasikmalaya - Virna Lestiyani; Wan Ridwan Husen; Asti Tri Lestari (Realisasi : Ilmu Pendidikan, Seni Rupa dan Desain, 2025)
In a study entitled "Analysis of Coloring Learning Using Crayons with the Drill Method for the Development of Fine Motor Skills of Early Childhood Aged 3-4 Years at Sanggar WARNA Tasikmalaya. One of the objectives of this study is to find out how the process of learning to color pictures using crayons with the drill method is like the development of fine motor skills of early childhood at Sanggar WARNA Tasikmalaya. In this study, the researcher focused on the process of learning to color pictures using crayons in early childhood and the results obtained from the learning at Sanggar WARNA Tasikmalaya. The researcher used a qualitative method with a descriptive analysis approach in his research, while the data collection was through field studies in the form of observations, interviews and documentation studies, which were then compiled, processed and analyzed to provide an overview of the existing problems. The results obtained by the researcher from the study, namely the process of learning to color using crayons with the drill method for the development of early childhood motor skills can help children to grow their concentration skills and also increase children's self-confidence. In the age range of 3-4 years, the child's learning process is more focused on coloring between 1, 2 or up to 3 color gradations. For the final results stage of learning, children are usually included in competitions, with the aim being more for evaluation needs rather than winning or losing.